The Narrative Study on the Students’ Vocabulary - Muslihin, Ade M. Amar (Papanda Journal of English Education, 2023)
This journal aims to find out how people have acquired a vocabulary of English. Whether an ancestry will have a big impact on someone’s English language acquisition. The researcher conducted research that used a qualitative approach using narrative study design on objects where he was proficient in English. Even though he has no ancestry at all, but with his enthusiasm and willingness to master English, he has also gone through various obstacles, likes, ridiculed by the surrounding community (especially by his friends). What is interesting is that he uses social media as a media to acquire the vocabulary. Keywords: Vocabulary Acquisition, Narrative Study, Language Mastery.